ABC Classification Analysis to Overcome the Overstock Problem at PT. Nutricia Indonesia Sejahtera - Saraswati, Anggita; Farmaciawaty, Desy Anisya (Journal of Business and Management, 2016)
Abstract.The research is done based on the PT. Nutricia Indonesia Sejahtera, a company that produces a formula milk located in Ciracas, Jakarta Timur. Nowdays, formula milk has become a complementary nutrition in the community and even as a substitute for ASI (Air Susu Ibu). PT. Nutricia Indonesia Sejahtera produces milk that is not only for the baby but also pregnant women and toddler. Since we know that the formula milk is really needed for all people, knowing the amount of inventory level is a must for company. The company experienced some problems related to the inventory management. This research will be analyse about the stock policy in the PT. Nutricia Indonesia Sejahtera. The company has a problem with an overstock problem for the raw material in the inventory. The objectives of this research is overcome the overstock problem in the warehouse and minimize the cost production in order to provide solutions to the company issues. In this research the author focus on the local and import raw material data products, the methods that will be used in this research is using Cycle Counting and ABC Classification Analysis. In the other hand, this research also provide the comparison between company and author calculation in order to compare which methods that gives advantages to the company.Â  The calculation for this research will involve Safety Stock, Re-order Point, Economic order quantity, Average Inventory Level in Rupiah and ABC Classification Analysis. In the ABC Classification analysis, the author also provide how to maintain the product by each classification.Analysis will give an advantages for the company such as overcome the overstock problem in the inventory and minimize the cost that have to be spend in one month. The author calculation and analysis is for import and local product. After calculate the data using Cycle Counting method, the author also calculate the ABC Classification Analysis to separate which product that is need more attention and maintenance. Knowing each classification by using ABC Classification will also reduce the cost that have to spend in one month, because the company will know which the product that has an expensive cost and lower cost, the author also provide how to keep the quality of each raw material based on their classification.Keywords : PT. Nutricia Indonesia Sejahtera, Overstock, Inventory, Economic Order Quantity.